ChemInform Abstract: Highly Efficient Microwave‐Assisted CO Aminocarbonylation with a Recyclable Pd(II)/TPP‐β‐Cyclodextrin Cross‐Linked Catalyst. Issue 35 (September 2015) - Calcio Gaudino, Emanuela; Carnaroglio, Diego; Martina, Katia; Palmisano, Giovanni; Penoni, Andrea; Cravotto, Giancarlo
Abstract A new recyclable catalytic system based on Pd(II) embedded in cross‐linked cyclodextrin is found to be very efficient in aminocarbonylation reactions of aryl iodides (I).